IMPLEMENTASI PEMBELAJARAN IPS BERBASIS KURIKULUM 2013 MELALUI LESSON STUDY DI SEKOLAH MUHAMMADIYAH KARTASURA - Tjipto Subadi; Kuswaji Dwi Priyono; Dahroni Dahroni; M. Musyiyam (Universitas Muhammadiyah Surakarta, 2015)
The purpose of this community service, assess and understand; 1) learning implementation strategy IPS (Social Sciences) Curriculum 2013 based on lesson study in the School of Muhammadiyah Kartasura. 2) Rationalization and elements of curriculum change in 2013. 3) The process of learning and assessment processes appropriate to the curriculum in 2013. The method used; workshops and training. The Place; SMK Muhammadiyah Kartasura. Execution time; odd semester 2014/2015. Subject: Elementary School teachers, Junior High School, High School and Vocational High School Muhammadiyah Kartasura. The results achieved; 1) learning implementation strategy IPS (Social Sciences) curriculum-based lesson study 203 through three stages, namely; plan (planning), do (action and observation), see (reflection). 2) Rationalization and elements of curriculum change in 2013 stressed on; a) The scientific approach is based approach to encourage student creativity; b)Integrity of the competence of knowledge, skills, and attitudes; c) Integrity of the curricular, co-curricular and extra-curricular activities. 3) The learning process is emphasized in the curriculum in 2013; (A) Integrated Thematic for elementary school level, (b) Approach Science (Natural Sciences) and IPS (Social Sciences) of partitive aggregative be integrated melt (liquid integrative), (c) religious and moral education, (d) learning objects; natural phenomena, social, and cultural arts. While the emphasisin the assessment process; assessment student achievement by using descriptive qualitative and quantitative numerical. Learning implementation strategy IPS (Social Sciences) 203 curriculum-based lesson study using a modified model of lesson study, achievement indicators for a significant increase from the prior worhshop and trainingafter the workshop, namely; 30%: 80% (pre-test: post-test).